Leiomyoma of the small bowel with ileovesical fistula. - de Almeida, J. Mendes; Santos, Víctor Melo (Acta Médica Portuguesa, 1979)
A case is reported in which a leiomyoma of the small bowel was revealed by an ileovesical fistula, complication of a benign tumor believed to be the first one in the literature. The mechanism of fistula formation is commented upon.